24.3k views
4 votes
Evaluate each expression if a=2, b=3 and c=4

A.) 2a+4b-c
B.) 6(a+c)-b

1 Answer

4 votes

Answer:

Explanation:

A.) 2a+4b-c: Replacing a with 2, b with 3 and c with 4, we get:

2(2) + 4(3) - (4) = 4 + 12 - 4 = 12

B.) 6(a+c)-b: Replacing a with 2 and c with 4, we get 6(2 + 4) - 3.

The work inside parentheses should be done first, resulting in 6(6) - 3.

This comes out to 33.

User Vittore Gravano
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.